Temporary meniscus extrusion is caused by cumulative stress from uphill and downhill tasks in healthy volunteers - Ishii, Yosuke; Okamoto, Saeko; Okinaka, Riko; Hashizume, Takato; Xu, Chen; Zhu, Kexin; Nakashima, Yuko; Okada, Kaoru; Takagi, Kazuya; Adachi, Nobuo; Takahashi, Makoto (Frontiers in Sports and Active Living, 2024)
Purpose: Excessive mechanical stress accumulates and causes knee injury. Meniscal extrusion is a key factor in detecting the reaction to cumulative mechanical stress. The cumulative stress strongly depends on environmental conditions such as flat and uphill/downhill, and cumulates in knee compartments; only a few studies have reported the effect of different environments on medial and lateral meniscus extrusion. This study aimed to investigate the effects of cumulative uphill/downhill stress on the meniscal extrusion in each compartment.Methods: Thirty healthy volunteers with 30 knees were involved in this cohort study (mean age, 22.0 ± 1.1 years; men, n=14). The participants were divided into flat-walking, uphill/downhill-walking, and uphill/downhill-jogging groups and their number of steps were recorded during the effort. Moreover, medial and lateral meniscal extrusions during walking were evaluated using ultrasound and performed three times, before and after efforts (T1) and (T2), and one day after efforts (T3), respectively.In the flat-walking group, no significant differences were observed between the follow-up periods. Conversely, in uphill/downhill-walking and jogging groups, the medial meniscus extrusion at T2 was significantly higher than that at T1. Conversely, MME at T3 was significantly lower than that at T2. In contrast, the lateral meniscus did not show any difference between the follow-up periods in any group.Temporary extrusion of the meniscus occurred after uphill/downhill tasks in healthy volunteers, and its reaction was observed only in the medial meniscus.